2020
DOI: 10.3390/su12041392
|View full text |Cite
|
Sign up to set email alerts
|

Customer Concentration, Economic Policy Uncertainty and Enterprise Sustainable Innovation

Abstract: Few studies have addressed how customer concentration affects the decision of a firm’s research and development (R&D) strategies and then innovation outcome. Using a sample of China’s listed companies for the period from 2009 to 2017, this study investigates the relationship between customer concentration and enterprise sustainable innovations, as well as how such the relationship changes with economic policy uncertainty. The findings imply that there is a significant inverted-U-shaped relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Enterprises' R&D investment plays an important role in enterprise innovation. Referring to the existing research, the ratio of R&D investment to operating income is adopted as the enterprise innovation index (Zhong et al. , 2020; Cumming et al ., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Enterprises' R&D investment plays an important role in enterprise innovation. Referring to the existing research, the ratio of R&D investment to operating income is adopted as the enterprise innovation index (Zhong et al. , 2020; Cumming et al ., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, a high customer concentration also means that firms may invest more in specific relationship when enhancing trust with their key customers. Once the uncertainty created by the Plan has an impact on the relationship with key customers, risk and significant costs occur to the focal firm, such as devaluation of specific funds (Zhong et al, 2020). Thirdly, customer concentration can affect corporate social responsibility (Wen et al, 2021).…”
Section: Customer Concentrationmentioning
confidence: 99%
“…With a high level of customer concentration, suppliers are more likely to make more significant relationship-specific investments to maintain such valuable relationships (Zhong et al, 2020). For instance, Wu (2015) found that Chinese suppliers were more committed to environmental conduct when they received pressure from multinational consumers than local consumers.…”
Section: Hypothesis Developmentmentioning
confidence: 99%